2018
DOI: 10.1590/1983-1447.2017.03.66012
|View full text |Cite
|
Sign up to set email alerts
|

Vacinação em pacientes com diabetes mellitus na atenção primária à saúde: cobertura e fatores associados

Abstract: RESUMO Objetivo Analisar a cobertura vacinal de pacientes com diabetes mellitus para as vacinas recomendadas pelo Programa Nacional de Imunizações e as variáveis associadas. Método Estudo transversal, com 255 pacientes de unidade básica de saúde, da região sudeste do Brasil, realizado em 2015. Utilizou-se o Sistema Informatizado de Gestão em Saúde para identificação da vacinação contra influenza, pneumococo, hepatite B, febre amarela, sarampo/caxumba/rubéola e difteria/tétano. Realizou-se análise estatísti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
6
0
5
Order By: Relevance
“…Despite the increased risk of vaccine-preventable diseases and international vaccination recommendations, several national studies have shown that DM patients’ vaccination coverage regarding the vaccines recommended by the National Immunization Program is below optimal, showing the vulnerability of this group to a considerable range of preventable diseases, as well as the need to increase immunization strategies for these patients. 36 , 37 , 38 , 39 , 40 This reduction in vaccination rates seems to be a global phenomenon, including in the pediatric age group. Studies have shown that the vaccination rate in children with DM is lower than that in healthy children and even in children with other chronic diseases, with disinformation being the main cause of the non-vaccination.…”
Section: Vaccination In the Dm Patientmentioning
confidence: 99%
“…Despite the increased risk of vaccine-preventable diseases and international vaccination recommendations, several national studies have shown that DM patients’ vaccination coverage regarding the vaccines recommended by the National Immunization Program is below optimal, showing the vulnerability of this group to a considerable range of preventable diseases, as well as the need to increase immunization strategies for these patients. 36 , 37 , 38 , 39 , 40 This reduction in vaccination rates seems to be a global phenomenon, including in the pediatric age group. Studies have shown that the vaccination rate in children with DM is lower than that in healthy children and even in children with other chronic diseases, with disinformation being the main cause of the non-vaccination.…”
Section: Vaccination In the Dm Patientmentioning
confidence: 99%
“…Arrelias et al 9 definiu o acompanhamento adequado da situação vacinal dos clientes com relação à Hepatite B pelos profissionais de saúde -e em especial, o enfermeiro -como uma das recomendações e prioridades do atendimento na rede de serviços de saúde. A análise de dois estudos de controle randomizados envolvendo grupos em situação de vulnerabilidade social evidenciou que o resultado da educação, combinados a incentivos à vacinação e um acompanhamento cuidadoso pelo enfermeiro, pode revelar uma tendência para o aumento das taxas de conclusão da vacinação da Hepatite B 13,18 .…”
Section: Discussionunclassified
“…No Brasil, as vacinas são oferecidas de forma gratuita pelo Sistema Único de Saúde (SUS), de acordo com um calendário vacinal, atualizado anualmente, com as vacinas que devem ser tomadas ao longo da vida. Grande parte das vacinas são tomadas na infância, mas algumas exigem reforço ao longo da vida, sendo importante estar sempre atento nas campanhas realizadas pelo SUS e na manutenção da carteira de vacinação em dia para melhor proteção 6 .…”
Section: Introductionunclassified
“…Existem também vacinas que não devem ser realizadas na gestante por trazer riscos ao feto, e são as vacinas tríplice viral, varicela, BCG e febre amarela, há exceção para as mulheres que moram ou irão viajar para áreas com foco de transmissão 6 .…”
Section: Introductionunclassified